Anastomotic leakage after upper gastrointestinal surgery: endoscopic treatment - Kähler, Georg (Visceral medicine, 2017)
Anastomotic leakages substantially influence the outcome of patients after major surgery of the upper gastrointestinal tract. Endoscopy is important for making a diagnosis and for managing anastomotic leakages. By means of endoscopic inspection of the anastomotic site, not only the size and position of dehiscences but also the blood supply of the anastomotic region and an imminent leakage can be assessed. To close anastomotic leakages, several therapeutic methods are available, i.e. stenting, clipping, and the application of glue. In the majority of cases, the endoscopic application of a sponge for permanent suction (endoscopic vacuum-assisted closure therapy) is promising.
Gesehen am 22.07.2018
Published online: June 14, 2017